1985
DOI: 10.1172/jci111766
|View full text |Cite
|
Sign up to set email alerts
|

Dietary and hormonal regulation of aldolase B gene expression.

Abstract: Aldolase B is an enzyme of the glycolytic pathway whose activity and mRNA levels in the liver fluctuate according to dietary status. Both the enzyme activity and the mRNA concentration decline during fasting and increase four-to eightfold upon refeeding of a carbohydrate-rich diet. The mechanism, however, of the mRNA induction remains unknown.To elucidate the mechanisms that regulate this induction responsive to dietary stimuli, we have studied the roles of hormones and glycolytic substrates on aldolase B gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 40 publications
(23 reference statements)
1
26
0
Order By: Relevance
“…[ZO]), T3 selectively inhibits or augments hepatic gene expression [17]. In fact, an enhancing effect has been communicated for the insulin or 'carbohydrate'-induced increase in hepatic gene expression for glucokinase [23], aldolase B [24], pyruvate kinase [25], acetyl-CoA carboxylase, fatty acid synthetase [26] and malic enzyme [27]. Our results, obtained for a T3-mediated effect at the nuclear level, extend the important role of thyroid hormones to the metabolic situation of gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…[ZO]), T3 selectively inhibits or augments hepatic gene expression [17]. In fact, an enhancing effect has been communicated for the insulin or 'carbohydrate'-induced increase in hepatic gene expression for glucokinase [23], aldolase B [24], pyruvate kinase [25], acetyl-CoA carboxylase, fatty acid synthetase [26] and malic enzyme [27]. Our results, obtained for a T3-mediated effect at the nuclear level, extend the important role of thyroid hormones to the metabolic situation of gluconeogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This was investigated by Munnich et al [65] and shown to differ in the three tissues expressing the enzyme. Starvation leads to a 10-fold decrease in mRNA concentration in liver and small intestine, but not in kidney.…”
Section: Nutritional and Hormonal Controlmentioning
confidence: 99%
“…Holoenzymes catalyse different reactions depending on the nature of the constituent subunits. Basically, aldolases A and C catalyze the cleavage of fructose-1, 6-bisphosphate in the glycolytic pathway, giving rise to glyceraldehyde-3-phosphate and dihydroacetate phosphate [4], [6], whereas aldolase B catalyses cleavage of fructose-1-phosphate derived from dietary carbohydrates to give rise to glyceraldehyde and dihydroacetate phosphate [6][7][8]. In addition, aldolase B catalyses gluconeogenesis or the hexose formation [7], [8].…”
Section: Introductionmentioning
confidence: 99%